2015
DOI: 10.1523/jneurosci.3924-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Morphology Generates High-Frequency Firing Resonance

Abstract: The attenuation of neuronal voltage responses to high-frequency current inputs by the membrane capacitance is believed to limit single-cell bandwidth. However, neuronal populations subject to stochastic fluctuations can follow inputs beyond this limit. We investigated this apparent paradox theoretically and experimentally using Purkinje cells in the cerebellum, a motor structure that benefits from rapid information transfer. We analyzed the modulation of firing in response to the somatic injection of sinusoida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
93
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(99 citation statements)
references
References 57 publications
6
93
0
Order By: Relevance
“…Two-compartment model. We also use a two-compartment model that contains one somatic compartment and one dendritic compartment (Ostojic et al, 2015). To allow for electrotonic coupling, both compartments are connected via an Ohmic conductance.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two-compartment model. We also use a two-compartment model that contains one somatic compartment and one dendritic compartment (Ostojic et al, 2015). To allow for electrotonic coupling, both compartments are connected via an Ohmic conductance.…”
Section: Methodsmentioning
confidence: 99%
“…A recent computational study by Eyal et al (2014) and in vitro experiments and modeling on Purkinje cells by Ostojic et al (2015) revealed that the presence of a purely passive dendritic tree can enhance the response at high frequencies. We tested whether similar models as used in these studies can reproduce, not only the rate modulation factor, but also all of the second-order statistics that were accessible in our in vivo experiments: spike train power spectrum, cross-spectra between stimulus and spike train and between two different spike trains (i.e., two different trials) for a frozen stimulus, and the coherence function.…”
Section: Two-compartment Model Can Reproduce Neuronal Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…Additional variables may describe synaptic filtering [11], external sources of colored noise [12,13], dendritic compartments [14], and subthreshold oscillations [15].…”
Section: Introductionmentioning
confidence: 99%